Conductive polymer aqueous solution and conductive polymer film
The aqueous conductive polymer solution, comprising self-doped polythiophene, polystyrene sulfonic acid, and a silane compound, addresses the limitations of existing films by enhancing water resistance, heat resistance, and conductivity, making it suitable for demanding applications.
Patent Information
- Application Number
- JP2021011055
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2021-01-27
- Publication Date
- 2025-04-02
- Estimated Expiration
- 2041-01-27
AI Technical Summary
Existing conductive polymer films lack sufficient water resistance and heat resistance, which limits their applications in harsh environments.
An aqueous conductive polymer solution containing water-soluble self-doped polythiophene, polystyrene sulfonic acid, and a silane compound, specifically formulated to enhance the conductivity, water resistance, and heat resistance of the resulting film.
The solution effectively produces a conductive polymer film with superior water resistance and heat resistance, maintaining high conductivity and durability in challenging conditions.
Smart Images

Figure 0007654987000001 
Figure 0007654987000002 
Figure 0007654987000003
Abstract
Description
[Technical field]
[0001] The present invention has been made in order to develop a conductive polymer aqueous solution capable of providing a conductive polymer having both water resistance and heat resistance, and relates to a conductive polymer aqueous solution containing a specific self-doped conductive polymer having high conductivity, a polystyrene sulfonate compound, and a silane compound, a conductive polymer film obtained by drying the conductive polymer aqueous solution, and an article coated with the conductive polymer film. [Background technology]
[0002] Conductive polymer materials have been developed in which π-conjugated polymers, such as polyacetylene, polythiophene, polyaniline, polypyrrole, etc., are doped with electron-accepting compounds as dopants, and applications thereof to, for example, antistatic agents, solid electrolytes for capacitors, conductive paints, electromagnetic wave shields, electrochromic elements, electrode materials, thermoelectric conversion materials, transparent conductive films, chemical sensors, actuators, etc. Among these conductive polymer materials, polythiophene-based conductive polymer materials are particularly useful in practical use from the standpoint of chemical stability.
[0003] Polythiophene-based conductive polymer materials include a PEDOT:PSS aqueous dispersion solution (a so-called externally doped conductive polymer) obtained by polymerizing 3,4-ethylenedioxythiophene (EDOT) in an aqueous solution of polystyrene sulfonic acid (PSS) as a dopant, and a so-called self-doped conductive polymer having a substituent (sulfo group, sulfonate group, etc.) that combines water solubility and doping action, directly or via a spacer, in the polymer main chain; for example, PEDOT-S is known (see, for example, Patent Document 1 and Non-Patent Documents 1 and 2).
[0004] Applications of conductive polymers have been widely investigated, particularly as antistatic agents and as solid electrolytes in solid electrolytic capacitors, and there have been reports of using conductive polymers to increase the capacity and reduce the ESR of solid electrolytic capacitors. [Prior art documents] [Patent documents]
[0005] [Patent Document 1] International Publication No. 2014 / 007299 [Non-patent literature]
[0006] [Non-Patent Document 1] Journal of American Chemical Society,112,2801-2803(1990) [Non-Patent Document 2] Advanced Materials,Vol.23(38)4403-4408(2011) Summary of the Invention [Problem to be solved by the invention]
[0007] An object of the present invention is to provide an aqueous conductive polymer solution that improves the water resistance and heat resistance of a conductive film containing a self-doped conductive polymer. [Means for solving the problem]
[0008] As a result of intensive research aimed at solving the above problems, the present inventors have found that an aqueous conductive polymer solution containing a water-soluble self-doped conductive polythiophene (A), a water-soluble polystyrene sulfonate compound (B), and a silane compound (C) specified in the present invention at specific concentrations can form a conductive film that is more water-resistant and heat-resistant than conventionally known compositions, and have completed the present invention.
[0009] That is, the present invention resides in the following.
[0010] [1] A conductive polymer aqueous solution comprising a polythiophene (A) containing at least one structural unit selected from the group consisting of a structural unit represented by the following general formula (1) and a structural unit represented by the following general formula (2), a polystyrene sulfonic acid compound (B), and a silane compound (C), wherein the content of (A) is 0.01 to 10% by weight, and the contents of (B) and (C) are each independently 0.001 to 30% by weight.
[0011] [ka]
[0012] [In the general formulas (1) and (2), R 2 represents a hydrogen atom, a methyl group, an ethyl group, a linear or branched alkyl group having 3 to 6 carbon atoms, or a fluorine atom, m represents an integer of 1 to 10, and n represents 0 or 1. [2] The conductive polymer aqueous solution according to the above-mentioned [1], wherein the polystyrene sulfonic acid compound (B) is a polystyrene sulfonic acid compound (B) having an average molecular weight of 1,000 to 1,000,000.
[0013] [3] The conductive polymer aqueous solution according to the above [1] or [2], characterized in that the polystyrene sulfonic acid compound (B) is polystyrene sulfonic acid which may have a substituent, a metal salt thereof, or an amine salt thereof, or a copolymer of a styrene sulfonic acid monomer which may have a substituent and another different monomer, a metal salt thereof, or an amine salt thereof.
[0014] [4] The conductive polymer aqueous solution according to the above-mentioned [1], characterized in that the silane compound (C) is an alkoxysilane compound having at least one substituent selected from the group consisting of an epoxy group and an amino group.
[0015] [5] A method for producing a film, comprising applying an aqueous solution of a conductive polymer according to any one of the above items [1] to [4] onto a support, and then drying the applied solution.
[0016] [6] A film comprising a polythiophene (A) containing at least one structural unit selected from the group consisting of a structural unit represented by the following formula (1) and a structural unit represented by the following formula (2), a polystyrene sulfonic acid compound (B), and a silane compound (C):
[0017] [ka]
[0018] [In the general formulas (1) and (2), R 2 represents a hydrogen atom, a methyl group, an ethyl group, a linear or branched alkyl group having 3 to 6 carbon atoms, or a fluorine atom, m represents an integer of 1 to 10, and n represents 0 or 1. Effect of the Invention
[0019] According to the present invention, it is possible to provide a conductive polymer membrane having excellent water resistance and heat resistance. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0020] The present invention will be described in detail below.
[0021] The conductive polymer aqueous solution of the present invention is an aqueous conductive polymer solution containing a polythiophene (A) containing at least one structural unit selected from the group consisting of a structural unit represented by the following general formula (1) and a structural unit represented by the following general formula (2), a polystyrene sulfonate compound (B), and a silane compound (C), characterized in that the content of (A) is 0.01 to 10% by weight, and the contents of (B) and (C) are each independently 0.001 to 30% by weight.
[0022] [ka]
[0023] [In the general formulas (1) and (2), R 2 represents a hydrogen atom, a methyl group, an ethyl group, a linear or branched alkyl group having 3 to 6 carbon atoms, or a fluorine atom, m represents an integer of 1 to 10, and n represents 0 or 1. In the above general formulas (1) and (2), R 2 represents a hydrogen atom, a methyl group, an ethyl group, a linear or branched alkyl group having 3 to 6 carbon atoms, or a fluorine atom.
[0024] The linear or branched alkyl group having 3 to 6 carbon atoms is not particularly limited, and examples thereof include an n-propyl group, an isopropyl group, an n-butyl group, an isobutyl group, a sec-butyl group, a tert-butyl group, an n-pentyl group, an isopentyl group, a neopentyl group, a tert-pentyl group, a cyclopentyl group, an n-hexyl group, a 2-ethylbutyl group, and a cyclohexyl group.
[0025] The above R 2 From the viewpoint of film-forming properties, it is preferable that is a hydrogen atom, a methyl group, an ethyl group, or a fluorine atom, and more preferably is a hydrogen atom or a methyl group.
[0026] In the above general formulas (1) and (2), m represents an integer of 1 to 10, and from the viewpoint of film-forming properties, it is preferably an integer of 1 to 6, more preferably an integer of 1 to 4, and even more preferably 2 or 3.
[0027] In the above general formulas (1) and (2), n is 0 or 1, with 1 being preferred from the standpoint of film-forming properties.
[0028] The structural unit represented by the above general formula (2) represents the doped state of the structural unit represented by the above general formula (1).
[0029] Dopants that cause an insulator-metal transition by doping can be divided into acceptors and donors. The former enters the vicinity of the polymer chain of a conductive polymer by doping and takes away π electrons from the conjugated system of the main chain. As a result, a positive charge (positive hole) is injected into the main chain, so it is also called a p-type dopant. Conversely, the latter donates an electron to the conjugated system of the main chain, and this electron moves through the conjugated system of the main chain, so it is also called an n-type dopant.
[0030] The dopant in the present invention is a sulfo group or a sulfonate group covalently bonded within the polymer molecule, and is a p-type dopant. A polymer that exhibits electrical conductivity without the addition of an external dopant is called a self-doped polymer.
[0031] The polythiophene (A) may be a commercially available product or may be synthesized based on publicly known information. The synthesis method is not particularly limited, but may be, for example, a method in which a thiophene monomer represented by the following general formula (3) is polymerized in water or an alcohol solvent in the presence of an oxidizing agent, and then, if necessary, treated with an acid.
[0032] [ka]
[0033] [In the above general formula (3), R 2 , m, and n are R in the above general formulas (1) and (2). 2 , m, and n are defined the same as above. M represents a hydrogen ion, an alkali metal ion, an ammonium ion, an organic ammonium ion, or a quaternary ammonium ion. In the above general formula (3), M represents a hydrogen ion, an alkali metal ion, an ammonium ion, an organic ammonium ion, or a quaternary ammonium ion.
[0034] The alkali metal ion is not particularly limited, but examples thereof include a lithium ion, a potassium ion, a sodium ion, a rubidium ion, and a cesium ion.
[0035] The organic ammonium ion is not particularly limited, and examples thereof include primary, secondary, or tertiary organic ammonium ions having a total carbon number of 1 to 30. More specifically, examples thereof include methylammonium, dimethylammonium, trimethylammonium, ethylammonium, triethylammonium, normal-propylammonium, isopropylammonium, normal-butylammonium, hexylammonium, 2-hydroxyethylammonium, N,N-dimethyl-N-(2-hydroxyethyl)ammonium, and N-methyl-N-(2-hydroxyethyl)ammonium. Examples of the ammonium ion include ammonium, di(2-hydroxyethyl)ammonium, N-methyl-N,N-di(2-hydroxyethyl)ammonium, N,N,N-tri(2-hydroxyethyl)ammonium, 2,3-dihydroxypropylammonium, N-methyl-N-(2,3-dihydroxypropyl)ammonium, N,N-dimethyl-N-(2,3-dihydroxypropyl)ammonium, 1,4-butanediammonium, triisobutylammonium, triisopentylammonium, triisooctylammonium, pyridinium ion, picolinium ion, and lutidinium ion.
[0036] The quaternary ammonium ion is not particularly limited, but examples thereof include a tetramethylammonium ion, a tetraethylammonium ion, a tetra-n-propylammonium ion, a tetra-n-butylammonium ion, and a tetra-n-hexylammonium ion.
[0037] For a polymer obtained after polymerization of a thiophene monomer represented by general formula (3) (wherein M is not a hydrogen ion), M can be converted to a hydrogen ion by acid treatment. The polymerization method and the method for converting M to a hydrogen ion are not particularly limited, and any method described in a publicly known document can be selected and carried out. By the conversion to a hydrogen ion, a polythiophene (A) containing at least one structural unit selected from the group consisting of the structural unit represented by general formula (1) and the structural unit represented by general formula (2) can be produced.
[0038] The thiophene monomer represented by the above general formula (3) is not particularly limited, but specifically includes sodium 3-[(2,3-dihydrothieno[3,4-b]-[1,4]dioxin-2-yl)methoxy]-1-propanesulfonate, potassium 3-[(2,3-dihydrothieno[3,4-b]-[1,4]dioxin-2-yl)methoxy]-1-propanesulfonate, sodium 3-[(2,3-dihydrothieno[3,4-b]-[1,4]dioxin-2-yl)methoxy]-1-methyl-1-propanesulfonate, sodium 3-[(2,3-dihydrothieno[3,4-b]-[1,4]dioxin-2-yl)methoxy]-1-methyl-1-propanesulfonate, Sodium thieno[3,4-b]-[1,4]dioxin-2-yl)methoxy]-1-ethyl-1-propanesulfonate, sodium 3-[(2,3-dihydrothieno[3,4-b]-[1,4]dioxin-2-yl)methoxy]-1-propyl-1-propanesulfonate, sodium 3-[(2,3-dihydrothieno[3,4-b]-[1,4]dioxin-2-yl)methoxy]-1-butyl-1-propanesulfonate, sodium 3-[(2,3-dihydrothieno[3,4-b]-[1,4]dioxin-2-yl)methoxy]-1-pentyl-1-propanesulfonate Sodium pansulfonate, sodium 3-[(2,3-dihydrothieno[3,4-b]-[1,4]dioxin-2-yl)methoxy]-1-hexyl-1-propanesulfonate, sodium 3-[(2,3-dihydrothieno[3,4-b]-[1,4]dioxin-2-yl)methoxy]-1-isopropyl-1-propanesulfonate, sodium 3-[(2,3-dihydrothieno[3,4-b]-[1,4]dioxin-2-yl)methoxy]-1-isobutyl-1-propanesulfonate, sodium 3-[(2,3-dihydrothieno[3,4-b]-[1,4]dioxin-2-yl)methoxy]-1-isobutyl-1-propanesulfonate, sodium 3-[(2,3-dihydrothieno[3,4-b]-[1, 4]dioxin-2-yl)methoxy]-1-isopentyl-1-propanesulfonic acid sodium salt, 3-[(2,3-dihydrothieno[3,4-b]-[1,4]dioxin-2-yl)methoxy]-1-fluoro-1-propanesulfonic acid sodium salt, 3-[(2,3-dihydrothieno[3,4-b]-[1,4]dioxin-2-yl)methoxy]-1-methyl-1-propanesulfonic acid potassium salt, 3-[(2,3-dihydrothieno[3,4-b]-[1,4]dioxin-2-yl)methoxy]-1-methyl-1-propanesulfonic acid, 3-[(2,3-Dihydrothieno[3,4-b]-[1,4]dioxin-2-yl)methoxy]-1-methyl-1-propanesulfonic acid ammonium salt, 3-[(2,3-dihydrothieno[3,4-b]-[1,4]dioxin-2-yl)methoxy]-1-methyl-1-propanesulfonic acid triethylammonium salt, 4-[(2,3-dihydrothieno[3,4-b]-[1,4]dioxin-2-yl)methoxy]-1-butanesulfonic acid sodium salt, 4-[(2,3-dihydrothieno[3,4-b]-[1,4]dioxin-2-yl)methoxy]-1-butanesulfonic acid sodium salt 4-[(2,3-dihydrothieno[3,4-b]-[1,4]dioxin-2-yl)methoxy]-1-butanesulfonic acid potassium salt, 4-[(2,3-dihydrothieno[3,4-b]-[1,4]dioxin-2-yl)methoxy]-1-methyl-1-butanesulfonic acid sodium salt, 4-[(2,3-dihydrothieno[3,4-b]-[1,4]dioxin-2-yl)methoxy]-1-methyl-1-butanesulfonic acid potassium salt, 4-[(2,3-dihydrothieno[3,4-b]-[1,4]dioxin-2-yl)methoxy]-1-fluoro-1-butanesulfonic acid sodium salt , 4-[(2,3-dihydrothieno[3,4-b]-[1,4]dioxin-2-yl)methoxy]-1-fluoro-1-butanesulfonic acid potassium, 6-(2,3-dihydro-thieno[3,4-b][1,4]dioxin-2-yl)hexane-1-sulfonic acid, 6-(2,3-dihydro-thieno[3,4-b][1,4]dioxin-2-yl)hexane-1-sulfonic acid sodium, 6-(2,3-dihydro-thieno[3,4-b][1,4]dioxin-2-yl)hexane-1-sulfonic acid lithium Examples include potassium 6-(2,3-dihydro-thieno[3,4-b][1,4]dioxin-2-yl)hexane-1-sulfonate, potassium 8-(2,3-dihydro-thieno[3,4-b][1,4]dioxin-2-yl)octane-1-sulfonic acid, sodium 8-(2,3-dihydro-thieno[3,4-b][1,4]dioxin-2-yl)octane-1-sulfonate, and potassium 8-(2,3-dihydro-thieno[3,4-b][1,4]dioxin-2-yl)octane-1-sulfonate.
[0039] In the present invention, the conductivity of the polythiophene (A) is not particularly limited, but it is preferable that the conductivity (electrical conductivity) in a film state is 10 S / cm or more.
[0040] In the conductive polymer aqueous solution of the present invention, the concentration of the polythiophene (A) containing at least one structural unit selected from the group consisting of the structural unit represented by the general formula (1) and the structural unit represented by the general formula (2) is 0.01 to 10% by weight. From the viewpoint of excellent conductivity, the concentration of the polythiophene (A) in the conductive polymer aqueous solution of the present invention is preferably 0.05% by weight or more, and from the viewpoint of excellent operability, it is preferably 8.0% by weight or less. That is, it is preferably 0.05 to 8% by weight, more preferably 0.1 to 7% by weight, more preferably 0.1 to 5% by weight, more preferably 0.1 to 3% by weight, and more preferably 0.1 to 2% by weight.
[0041] The polythiophene (A) used in the present invention may be one synthesized based on publicly known information.
[0042] The polystyrene sulfonic acid compound (B) in the present invention may be a homopolymer (single polymer) or a copolymer (copolymerization product) in which styrene sulfonic acid, which may have a substituent, is a monomer, and may be an acid type compound or a salt compound. There is no particular restriction on the number or type of different monomers in the copolymer, and there is no particular restriction on the ratio of acid residues and salt residues.
[0043] The polystyrene sulfonic acid compound (B) in the present invention may be a commercially available product or one produced by a generally known method.
[0044] The polystyrene sulfonic acid compound (B) used in the present invention is not particularly limited. However, the average molecular weight is preferably in the range of 1,000 to 1,000,000, and more preferably in the range of 10,000 to 800,000.
[0045] The type of polystyrene sulfonic acid compound (B) used in the present invention is not particularly limited, and examples thereof include polystyrene sulfonic acid which may have a substituent, a metal salt thereof, or an amine salt thereof, or a copolymer of a styrene sulfonic acid monomer which may have a substituent and another different monomer, a metal salt thereof, or an amine salt thereof.
[0046] The polystyrene sulfonic acid which may have a substituent is not particularly limited, but may be, for example, polystyrene sulfonic acid or polystyrene sulfonic acid having a substituent. The substituent is not particularly limited, but may be, for example, a methyl group, an ethyl group, a methoxy group, an ethoxy group, a methoxymethyl group, a hydroxy group, a cyano group, a nitro group, a halogen atom (a fluorine atom, a chlorine atom, a bromine atom, an iodine atom), an amino group, or a carboxy group.
[0047] The styrene sulfonic acid monomer which may have the above-mentioned substituent is not particularly limited, but may be, for example, styrene sulfonic acid or styrene sulfonic acid having a substituent. The above-mentioned substituent is not particularly limited, but may be, for example, methyl group, ethyl group, methoxy group, ethoxy group, methoxymethyl group, hydroxy group, cyano group, nitro group, halogen atom (fluorine atom, chlorine atom, bromine atom, iodine atom), amino group, or carboxy group.
[0048] Examples of the other heterogeneous monomers include, but are not limited to, styrene which may have a substituent (e.g., styrene, p-fluorostyrene, p-methoxystyrene, p-butoxystyrene, or p-vinylbenzoic acid, etc.), acrylic acid which may have a substituent (e.g., acrylic acid, methyl acrylate, ethyl acrylate, hydroxyethyl acrylate, 2-ethylhexyl acrylate, or dimethylaminoethyl acrylate, etc.), methacrylic acid which may have a substituent (e.g., methacrylic acid, methyl methacrylate, ethyl methacrylate, hydroxyethyl methacrylate, 2-ethylhexyl methacrylate, or dimethylaminoethyl methacrylate, etc.), αβ-unsaturated carboxylic acid compounds (e.g., maleic anhydride, N-phenylmaleimide, N-methylmaleimide, N-ethylmaleimide, N-butylmaleimide, N-cyclohexylmaleimide, N-benzylmaleimide, etc.), and N-vinylpyrrolidone. Of these, styrene, p-butoxystyrene, and methyl methacrylate are preferred.
[0049] That is, the copolymer of the styrenesulfonic acid monomer which may have the above-mentioned substituent in the polystyrenesulfonic acid compound (B) and another different monomer is not particularly limited, and examples thereof include styrenesulfonic acid / styrene copolymer, styrenesulfonic acid / p-fluorostyrene copolymer, styrenesulfonic acid / p-methoxystyrene copolymer, styrenesulfonic acid / p-butoxystyrene copolymer, styrenesulfonic acid / p-vinylbenzoic acid copolymer, styrenesulfonic acid / acrylic acid copolymer, styrenesulfonic acid / methyl acrylate copolymer, styrenesulfonic acid / ethyl acrylate copolymer, styrenesulfonic acid / hydroxyethyl acrylate copolymer, styrenesulfonic acid / 2-ethylhexyl acrylate copolymer, styrenesulfonic acid / dimethylaminoethyl acrylate copolymer, styrenesulfonic acid / methacrylic acid copolymer, styrenesulfonic acid / methyl methacrylate copolymer, styrenesulfonic acid / ethyl ... Examples of the copolymer include styrene sulfonic acid / hydroxyethyl methacrylate copolymer, styrene sulfonic acid / 2-ethylhexyl methacrylate copolymer, styrene sulfonic acid / dimethylaminoethyl methacrylate copolymer, styrene sulfonic acid / maleic anhydride copolymer, styrene sulfonic acid / N-phenylmaleimide copolymer, styrene sulfonic acid / N-methylmaleimide copolymer, styrene sulfonic acid / N-ethylmaleimide copolymer, styrene sulfonic acid / N-butylmaleimide copolymer, styrene sulfonic acid / N-cyclohexylmaleimide copolymer, styrene sulfonic acid / N-benzylmaleimide copolymer, styrene sulfonic acid / N-vinylpyrrolidone copolymer, or styrene sulfonic acid / styrene / methyl methacrylate copolymer, and among these, styrene sulfonic acid / styrene copolymer, styrene sulfonic acid / p-butoxystyrene copolymer, or styrene sulfonic acid / methyl methacrylate copolymer are preferred. The copolymer may be a block copolymer, a random copolymer, or an alternating polymer.
[0050] From the viewpoint of excellent film-forming properties, the polystyrene sulfonic acid compound (B) of the present invention preferably contains polystyrene sulfonic acid, a metal salt thereof, or an amine salt thereof, or a styrene sulfonic acid copolymer selected from the group consisting of a styrene sulfonic acid / styrene copolymer, a styrene sulfonic acid / p-butoxystyrene copolymer, and a styrene sulfonic acid / methyl methacrylate copolymer, a metal salt thereof, or an amine salt thereof.
[0051] The metal salt is not particularly limited, but examples thereof include sodium salt, potassium salt, and lithium salt. The amine in the amine salt is not particularly limited, but examples thereof include the same amine compounds in the conjugate acid of the amine compound described below, and the same applies to the preferred amine compounds.
[0052] The conductive polymer aqueous solution of the present invention contains 0.001 to 30% by weight of a polystyrene sulfonic acid compound (B). In terms of excellent film adhesion, the content is preferably 0.01 to 20% by weight, more preferably 0.1 to 10% by weight, more preferably 0.1 to 5% by weight, more preferably 0.1 to 3% by weight, and more preferably 0.1 to 1% by weight.
[0053] In terms of excellent pH stability, the content of the polystyrene sulfonic acid compound (B) in the conductive polymer aqueous solution of the present invention is preferably 10 parts by weight to 300 parts by weight, and more preferably 25 parts by weight to 200 parts by weight, per 100 parts by weight of the polythiophene (A).
[0054] The conductive polymer aqueous solution of the present invention is characterized by further containing 0.001 to 30% by weight of a silane compound (C).
[0055] The silane compound (C) is not particularly limited, but examples thereof include silane compounds having a chlorosilyl group, an acylsilyl group, an alkoxysilyl group, etc. (these compounds may have at least one substituent selected from the group consisting of a vinyl group, a methacryl group, a mercapto group, an epoxy group, and an amino group). In terms of ease of handling, silane compounds having an alkoxysilyl group (these compounds may have at least one substituent selected from the group consisting of a vinyl group, a methacryl group, a mercapto group, an epoxy group, and an amino group) are preferred, and in terms of reactivity, silane compounds having a methoxysilyl group or an ethoxysilyl group (these compounds may have at least one substituent selected from the group consisting of a vinyl group, a methacryl group, a mercapto group, an epoxy group, and an amino group) are particularly preferred.
[0056] Specific examples of the silane compound (C) include, but are not limited to, 2-(3,4-epoxycyclohexyl)ethyltrimethoxysilane, 3-glycidoxypropylmethyldimethoxysilane, 3-glycidoxypropyltrimethoxysilane, 3-glycidoxypropylmethyldiethoxysilane, 3-glycidoxypropyltriethoxysilane, 3-glycidoxybutyltrimethoxysilane, vinyltrimethoxysilane, vinyltriethoxysilane, para-styryltrimethoxysilane, 3-methacryloxypropylmethyldimethoxysilane, 3-methacryloxypropyltrimethoxysilane, 3-methacryloxypropylmethyldiethoxysilane, 3-methacryloxypropyltriethoxysilane, 3-acryloxypropyl Examples of the silane include pyltrimethoxysilane, N-2-(aminoethyl)-3-aminopropylmethyldimethoxysilane, N-2-(aminoethyl)-3-aminopropyltrimethoxysilane, 3-aminopropyltrimethoxysilane, 3-aminopropyltriethoxysilane, 3-triethoxysilyl-N-(1,3-dimethyl-butylidene)propylamine, N-phenyl-3-aminopropyltrimethoxysilane, 3-ureidopropyltrialkoxysilane, 3-isocyanatepropyltriethoxysilane, tris-(trimethoxysilylpropyl)triethoxysilane, tris-(trimethoxysilylpropyl)isocyanurate, 3-mercaptopropylmethyldimethoxysilane, 3-mercaptopropyltrimethoxysilane, etc. These may be used alone or in a mixture of two or more.
[0057] From the viewpoint of excellent film-forming properties, the silane compound (C) is preferably an alkoxysilane compound having at least one substituent selected from the group consisting of a vinyl group, a methacryl group, a mercapto group, an epoxy group, and an amino group, more preferably an alkoxysilane compound having at least one substituent selected from the group consisting of an epoxy group and an amino group, and more preferably 3-glycidoxypropyltrimethoxysilane or 3-aminopropyltrimethoxysilane.
[0058] The conductive polymer aqueous solution of the present invention contains 0.001 to 30% by weight of the silane compound (C). In terms of excellent film adhesion, the content is preferably 0.01 to 20% by weight, more preferably 0.1 to 10% by weight, more preferably 0.1 to 5% by weight, more preferably 0.1 to 3% by weight, and more preferably 0.1 to 1% by weight.
[0059] In terms of excellent pH stability, the content of the silane compound (C) in the aqueous conductive polymer solution of the present invention is preferably 10 parts by weight to 300 parts by weight, and more preferably 25 parts by weight to 200 parts by weight, per 100 parts by weight of the polythiophene (A).
[0060] The conductive polymer aqueous solution of the present invention is characterized by containing the above-mentioned (A), (B), and (C), and may further contain another compound in addition to these. The other compound is not particularly limited, but examples thereof include at least one surfactant (D) selected from the group consisting of nonionic surfactants and amphoteric surfactants, at least one water-soluble compound (E) selected from the group consisting of alcohols and water-soluble resins, and / or a compound (F) capable of forming an ion pair with the sulfonic acid group of the polythiophene (A).
[0061] The nonionic surfactant is not particularly limited, but examples thereof include polyethylene glycol type surfactants, acetylene glycol type surfactants, polyhydric alcohol type surfactants, and polymer type nonionic surfactants.
[0062] The polyethylene glycol surfactant is not particularly limited, but examples thereof include ethylene oxide adducts of higher alcohols, ethylene oxide adducts of alkylphenols, ethylene oxide adducts of fatty acids, ethylene oxide adducts of polyhydric alcohol fatty acid esters, ethylene oxide adducts of higher alkylamines, ethylene oxide adducts of fats and oils, and ethylene oxide adducts of polypropylene glycols.
[0063] Examples of the acetylene glycol surfactant include 2,4,7,9-tetramethyl-5-decyne-4,7-diol, Surfynol (registered trademark, manufactured by Air Products Co., Ltd.), and Olfine (registered trademark, manufactured by Nissin Chemical Industry Co., Ltd.).
[0064] The polyhydric alcohol surfactant is not particularly limited, but examples thereof include fatty acid esters of glycerol, fatty acid esters of pentaerythritol, fatty acid esters of sorbitol and sorbitan, fatty acid esters of sucrose, alkyl ethers of higher alcohols, and fatty acid amides of alkanolamines.
[0065] The polymeric nonionic surfactant is not particularly limited, but examples thereof include polyvinylpyrrolidone and a copolymer of polyvinylpyrrolidone. The average molecular weight of the polyvinylpyrrolidone used in the present invention is 1,000 to 2,000,000, preferably 10,000 to 1,500,000. The copolymer of polyvinylpyrrolidone is not particularly limited, but is preferably one having both a hydrophilic part and a hydrophobic part in the polymer chain, and examples thereof include a copolymer in which polyvinylpyrrolidone is grafted to polyvinyl alcohol, a [vinylpyrrolidone-vinyl acetate] block copolymer, a [vinylpyrrolidone-methyl methacrylate] copolymer, a [vinylpyrrolidone-normal butyl methacrylate] copolymer, or a [vinylpyrrolidone-acrylamide] copolymer.
[0066] The amphoteric surfactant is not particularly limited, but examples thereof include betaine-type amphoteric surfactants, fluorine-based surfactants, and silicone-based surfactants.
[0067] The betaine type amphoteric surfactant is not particularly limited, but examples thereof include alkyl dimethyl betaine, lauryl dimethyl betaine, stearyl dimethyl betaine, and lauryl dihydroxyethyl betaine.
[0068] The fluorosurfactant is not particularly limited as long as it has a perfluoroalkyl group, and examples thereof include perfluoroalkanes, perfluoroalkyl carboxylic acids, perfluoroalkyl sulfonic acids, and perfluoroalkyl ethylene oxide adducts.
[0069] The silicone surfactant is not particularly limited, but examples thereof include polyether-modified polydimethylsiloxane, polyetherester-modified polydimethylsiloxane, hydroxyl group-containing polyether-modified polydimethylsiloxane, acrylic group-containing polyether-modified polydimethylsiloxane, acrylic group-containing polyester-modified polydimethylsiloxane, perfluoropolyether-modified polydimethylsiloxane, perfluoropolyester-modified polydimethylsiloxane, and silicone-modified acrylic compounds.
[0070] Fluorine-based surfactants and silicone-based surfactants are effective as leveling agents for improving the flatness of the coating film.
[0071] In the present invention, the surfactant (D) preferably has a solubility in water of 0.01% by weight or more and an HLB value in the range of 7-20.
[0072] The Griffin HLB (Hydrophile-Lipophile Balance) is a value that indicates the hydrophilicity of a surfactant. The higher the value, the greater the hydrophilicity, and is expressed by the following formula:
[0073] Griffin method HLB of nonionic surfactants = (molecular weight of hydrophilic group portion) / (molecular weight of surfactant) x 100 / 5 = (weight of hydrophilic group) / (weight of hydrophobic group + weight of hydrophilic group) x 100 / 5 = (weight % of hydrophilic group) / 5 In the present invention, the surfactant (D) is more preferably an acetylene glycol type surfactant or a polymer type surfactant.
[0074] The surfactant (D) may be added to the aqueous conductive polymer solution in the form of a solid, or may be added after being prepared as an aqueous solution in advance. In this case, the surfactant may be added to the aqueous conductive polymer solution alone, or two or more kinds of surfactants may be added in combination.
[0075] In the conductive polymer aqueous solution of the present invention, the content of at least one surfactant (D) selected from the group consisting of nonionic surfactants and amphoteric surfactants is preferably 0.001 to 10% by weight, and more preferably 0.1 to 5% by weight, in terms of excellent film-forming properties.
[0076] When the conductive polymer aqueous solution of the present invention contains a surfactant (D), the conductive polymer aqueous solution preferably contains 0.1 to 10% by weight of the polythiophene (A), 0.001 to 30% by weight of the polystyrene sulfonic acid compound (B), 0.001 to 30% by weight of the silane compound (C), and 0.001 to 10% by weight of the surfactant (D).
[0077] As described above, the conductive polymer aqueous solution of the present invention may contain at least one water-soluble compound (E) selected from the group consisting of alcohols and water-soluble resins.
[0078] The alcohol is not particularly limited, but examples thereof include at least one alcohol selected from the group consisting of monohydric alcohols, dihydric alcohols, trihydric alcohols, and sugar alcohols.
[0079] The monohydric alcohol is not particularly limited, but examples thereof include methanol, ethanol, 1-propanol, isopropanol, butanol, methoxyethanol, ethoxyethanol, butoxyethanol (butyl cellosolve), etc., and from the viewpoint of operability, ethanol, butyl cellosolve, or hexyl cellosolve is preferred. The dihydric alcohol is not particularly limited, but from the viewpoint of availability, ethylene glycol is preferred. The trihydric alcohol is not particularly limited, but for example, glycerol is preferred. The sugar alcohol is not particularly limited, but for example, erythritol, sorbitol, or arabitol is preferred. Sorbitol is more preferred.
[0080] In addition, the water-soluble resin is preferably one that has substantially no surfactant action. Although not particularly limited, for example, polyvinyl alcohol, polyacrylamide, polyvinylpyrrolidone (limited to those that have no surfactant action), poly(N-vinylacetamide), water-soluble polyester, water-soluble polyurethane, etc. are preferable. In addition, from the viewpoint of reducing the amount of metal, it is preferable to use these water-soluble resins that have been subjected to a metal removal filter treatment using a granular or membrane-like cation exchange resin or a zeta potential.
[0081] The molecular weight of the water-soluble resin is not particularly limited as long as it has good water solubility, but is preferably in the range of Mw=1,000 to 2,000,000, more preferably 10,000 to 1,500,000, even more preferably Mw=1,000 to 250,000, and even more preferably 1,000 to 100,000.
[0082] When the conductive polymer aqueous solution of the present invention contains the water-soluble compound (E), it preferably contains 0.001 to 30% by weight, and more preferably contains 0.01 to 25% by weight.
[0083] As described above, the conductive polymer aqueous solution of the present invention may further contain a compound (F) capable of forming an ion pair with the sulfonic acid group of the polythiophene (A) in terms of excellent film-forming properties. The compound (F) capable of forming an ion pair with the sulfonic acid group is not particularly limited, but examples thereof include alkali metal compounds, ammonia, organic amine compounds, and quaternary ammonium salts, and these compounds can react with the sulfonic acid group of the polythiophene (A) to form alkali metal ion salts, ammonium ion salts, organic ammonium ion salts, and quaternary ammonium ion salts of the polythiophene (A), respectively.
[0084] The alkali metal compound is not particularly limited, but examples thereof include alkali metal salt compounds (e.g., lithium chloride, potassium chloride, sodium chloride, rubidium chloride, cesium chloride, lithium bromide, potassium bromide, sodium bromide, rubidium bromide, cesium bromide, etc.) and alkali metal hydroxides (e.g., lithium hydroxide, potassium hydroxide, sodium hydroxide, rubidium hydroxide, cesium hydroxide, etc.).
[0085] The alkali metal ion salt of the lithiophene (A) can be prepared by adding the alkali metal compound to the conductive polymer aqueous solution of the present invention. The alkali metal ion is not particularly limited, but examples thereof include lithium ion, potassium ion, sodium ion, rubidium ion, and cesium ion.
[0086] The organic amine compound is not particularly limited, and examples thereof include primary, secondary, or tertiary organic amine compounds having a total carbon number of 1 to 30. More specific examples thereof include methylamine, dimethylamine, trimethylamine, ethylamine, triethylamine, normal-propylamine, isopropylamine, normal-butylamine, hexylamine, aminoethanol, dimethylaminoethanol, methylaminoethanol, diethanolamine, N-methyldiethanolamine, triethanolamine, 3-amino-1,2-propanediol, 3-methylamino-1,2-propanediol, 3-dimethylamino-1,2-propanediol, 1,4-butanediamine, triisobutylamine, triisopentylamine, triisooctylamine, imidazole, N-methylimidazole, 1,2-dimethylimidazole, pyridine, picoline, and lutidine.
[0087] By adding the organic amine compound to the conductive polymer aqueous solution of the present invention, the organic amine compound reacts with the polythiophene (A) to become an organic ammonium ion, and an organic ammonium ion salt of the polythiophene (A) is prepared. The organic ammonium ion is not particularly limited, but examples thereof include primary, secondary, and tertiary organic ammonium ions having a total carbon number of 1 to 30. More specifically, examples of the organic ammonium ion include methylammonium, dimethylammonium, trimethylammonium, ethylammonium, triethylammonium, normal-propylammonium, isopropylammonium, normal-butylammonium, hexylammonium, 2-hydroxyethylammonium, N,N-dimethyl-N-(2-hydroxyethyl)ammonium, N-methyl-N-(2-hydroxyethyl)ammonium, di(2-hydroxyethyl)ammonium, and the like. ammonium, N-methyl-N,N-di(2-hydroxyethyl)ammonium, N,N,N-tri(2-hydroxyethyl)ammonium, 2,3-dihydroxypropylammonium, N-methyl-N-(2,3-dihydroxypropyl)ammonium, N,N-dimethyl-N-(2,3-dihydroxypropyl)ammonium, 1,4-butanediammonium, triisobutylammonium, triisopentylammonium, triisooctylammonium, imidazole cation, N-methylimidazole cation, 1,2-dimethylimidazole cation, pyridinium ion, picolinium ion, or lutidinium ion.
[0088] The quaternary ammonium compound is not particularly limited, but examples thereof include tetramethylammonium chloride, tetraethylammonium chloride, tetra-n-propylammonium chloride, tetra-n-butylammonium chloride, and tetra-n-hexylammonium chloride.
[0089] By adding the quaternary ammonium compound to the conductive polymer aqueous solution of the present invention, the quaternary ammonium compound reacts with the polythiophene (A) to form a quaternary ammonium ion, and a quaternary ammonium ion salt of the polythiophene (A) is prepared. The quaternary ammonium ion is not particularly limited, but examples thereof include tetramethylammonium ion, tetraethylammonium ion, tetra-n-propylammonium ion, tetra-n-butylammonium ion, and tetra-n-hexylammonium ion.
[0090] When the conductive polymer aqueous solution of the present invention contains the compound (E), the content of the compound (F) is preferably 0.001 to 20% by weight, and from the viewpoint of excellent film-forming property, the content is preferably 0.01 to 15% by weight, and more preferably 0.1 to 10% by weight.
[0091] When the conductive polymer aqueous solution of the present invention contains the compound (F), a part or all of the polythiophene (A) containing at least one structural unit selected from the group consisting of the structural unit represented by the general formula (1) and the structural unit represented by the general formula (2) interacts with a part or all of the compound (F) to form a polythiophene (A) containing at least one structural unit selected from the group consisting of the structural unit represented by the general formula (1') and the structural unit represented by the general formula (2'). That is, a mixture of the polythiophene (A) containing at least one structural unit selected from the group consisting of the structural unit represented by the general formula (1) and the structural unit represented by the general formula (2) and the compound (F) and the polythiophene (A) containing at least one structural unit selected from the group consisting of the structural unit represented by the general formula (1') and the structural unit represented by the general formula (2') are the same.
[0092] [ka]
[0093] [In the above general formula (1') and general formula (2'), R 2 The definitions and preferred ranges of m and n are as shown in the above general formula (1) and general formula (2) R 2 The definitions and preferred ranges of n and m are the same as those of n. M represents a hydrogen ion, an alkali metal ion, an ammonium ion, an organic ammonium ion, or a quaternary ammonium ion. The alkali metal ion, ammonium ion, organic ammonium ion, and quaternary ammonium ion in M are as described above.
[0094] The pH of the conductive polymer aqueous solution of the present invention is preferably 10 or less, and more preferably 9 or less. Furthermore, the pH of the conductive polymer aqueous solution of the present invention is preferably in the range of 1.5 to 9.5, and more preferably in the range of 1.5 to 9. Here, the procedure for adjusting the pH is not particularly limited, but examples thereof include a method of controlling the type and amount of the compound (F) added.
[0095] The method for preparing the conductive polymer aqueous solution of the present invention is not particularly limited, and examples thereof include a method of mixing at least an aqueous solution or solid of the polythiophene (A), the polystyrene sulfonic acid compound (B), the silane compound (C), and additional water as necessary in any order and by any method.
[0096] In this case, at least one surfactant (D) selected from the group consisting of the nonionic surfactants and amphoteric surfactants, at least one water-soluble compound (E) selected from the group consisting of the alcohols and water-soluble resins, and the compound (F) capable of forming an ion pair with the sulfonic acid group of the polythiophene (A) can each be independently mixed in any amount, in any order, and by any method with the aqueous conductive polymer solution of the present invention.
[0097] The temperature during mixing is not particularly limited, but may be, for example, room temperature to heated, preferably 0° C. or higher and 100° C. or lower.
[0098] The atmosphere in which the mixture is mixed is not particularly limited, but may be either air or an inert gas.
[0099] When mixing the conductive polymer aqueous solution of the present invention, ultrasonic irradiation or homogenization treatment (for example, using a mechanical homogenizer, ultrasonic homogenizer, high-pressure homogenizer, etc.) may be performed in addition to a general mixing and dissolving operation using a stirrer tip, stirring blade, etc. When homogenization treatment is performed, it is preferable to perform it while cooling or heating in order to prevent thermal deterioration of the polymer.
[0100] The concentration of the conductive polymer aqueous solution of the present invention may be adjusted by the blending ratio, or may be adjusted by concentrating the solution after blending. The concentrating method may be a method of distilling off the solvent under reduced pressure, or a method of using an ultrafiltration membrane.
[0101] The concentration of polythiophene (A) in the aqueous conductive polymer solution of the present invention is not particularly limited as long as it is 0.001% by weight or more, but is preferably in the range of 0.01% by weight to 10% by weight. The aqueous conductive polymer solution of the present invention containing polythiophene (A), water-soluble polystyrene sulfonic acid compound (B) and silane compound (C) can be coated on a support and then dried and dehydrated to produce an aqueous conductive polymer film.
[0102] The particle size of the solid content in the conductive polymer aqueous solution of the present invention is not particularly limited, but the smaller the particle size, the better the water solubility, which is also desirable from the viewpoint of conductivity and uniform film formation during film formation. For example, when the solid content concentration of the conductive polymer aqueous solution prepared at room temperature or under heating is 10% by weight or less, the water solubility is better if the particle size (D50) of the solid content is 0.02 μm or less.
[0103] The viscosity (20°C) of the conductive polymer aqueous solution of the present invention is a very important factor during production and use. The effects of high viscosity during production and use include loss during stirring and liquid transfer, and prolonged use. There are no particular limitations as long as it is 250 mPa·s or less, but it is preferably 100 mPa·s or less, and more preferably 50 mPa·s or less.
[0104] The method for forming a conductive polymer film from the conductive polymer aqueous solution of the present invention is not particularly limited, but may be, for example, a method in which the conductive polymer aqueous solution of the present invention is applied to a support and dried. By carrying out this method, a conductive polymer film can be easily obtained on a support (hereinafter, the support and the conductive polymer film are collectively referred to as a "coated article").
[0105] The support is not particularly limited as long as the conductive polymer aqueous solution of the present invention can be applied thereto, and examples thereof include polymer substrates and inorganic substrates. Examples of the polymer substrates include thermoplastic resins, nonwoven fabrics, paper, resist film substrates, etc. Examples of the thermoplastic resins include polyethylene, polypropylene, polyethylene terephthalate, polyacrylate, polycarbonate, etc. Examples of the nonwoven fabrics include natural fibers, synthetic fibers, and glass fibers. The paper may be one mainly composed of general cellulose. Examples of the inorganic substrates include glass, ceramics, aluminum oxide, tantalum oxide, etc.
[0106] Examples of the method for applying the conductive polymer aqueous solution include casting, dipping, bar coating, dispenser, roll coating, gravure coating, flexographic printing, spray coating, spin coating, and inkjet printing. Spin coating is preferred.
[0107] The drying temperature for the coating film is not particularly limited as long as it is a temperature at which a uniform conductive polymer film is obtained and is equal to or lower than the heat resistance temperature of the substrate, but is in the range of room temperature to 300°C, preferably in the range of room temperature to 250°C, and more preferably in the range of room temperature to 200°C.
[0108] The drying atmosphere may be any of air, inert gas, vacuum, and reduced pressure, but from the viewpoint of preventing deterioration of the polymer film, an inert gas atmosphere such as nitrogen or argon is preferred.
[0109] The thickness of the resulting conductive polymer film is not particularly limited, but is preferably 10 -3 ~10 2 The range of 10 μm is preferable. -3 ~10 -1 μm.
[0110] The coated articles of the invention are used, for example, as antistatic films or solid electrolytes for solid or hybrid electrolytic capacitors. EXAMPLES
[0111] Examples of the present invention are given below.
[0112] The analytical instruments and measurement methods used in the examples are listed below.
[0113] [GC measurement] Equipment: Shimadzu, GC-2014.
[0114] [NMR measurement] Equipment: Gemini-200, manufactured by VARIAN.
[0115] [Surface resistivity measurement] Apparatus: Mitsubishi Chemical Loresta GP MCP-T600.
[0116] [Film thickness measurement] Equipment: DEKTAK XT manufactured by BRUKER. [Viscosity measurement] Complete viscometer / BROOKFIELD VISCOMETER DV-1 Prime.
[0117] [conductivity] Conductivity [S / cm]=10 4 / (Surface resistivity [Ω / □]×film thickness [μm]).
[0118] [Particle size measurement] Apparatus: Nikkiso Microtrac Nanotrac UPA-UT151. [Conductivity measurement of self-doped conductive polymer (A)] 0.5 mL of an aqueous solution containing a self-doped conductive polymer was applied to a 25 mm square non-alkali glass plate, dried overnight at room temperature, and then heated on a hot plate at 120°C for 20 minutes and then at 160°C for 10 minutes to obtain a conductive polymer film. The conductivity was calculated from the film thickness and surface resistance.
[0119] [Conductivity measurement of conductive polymer film] 0.5 mL of the conductive polymer aqueous solution of the present invention was applied to a 25 mm square alkali-free glass plate, dried at room temperature overnight, and then heated on a hot plate at 150° C. for 30 minutes and then at 200° C. for 30 minutes to obtain a conductive polymer film. The conductivity was calculated from the film thickness and surface resistance value.
[0120] [Water resistance evaluation] A conductive film prepared by the same procedure as in the measurement of the conductivity of the conductive polymer aqueous solution of the present invention was immersed in water and treated at 80°C for 60 minutes. A film in which the coating film dissolved or did not dissolve but fell off from the substrate was rated as poor, and a film in which the coating film did not dissolve or fall off was rated as good.
[0121] [Heat resistance evaluation] For a conductive film prepared by the same procedure as that for measuring the conductivity of the conductive polymer aqueous solution of the present invention, the initial surface resistance (SR0) was measured using Mitsubishi Chemical's Loresta GP MCP-T600, and the conductive film was then left to stand at 150°C for 60 hours in ETTAS's EOP-450B (programmed constant temperature dryer), after which the surface resistance (SR) was measured again. The rate of change (SR / SR0) of the surface resistance (SR) from the initial surface resistance (SR0) was calculated.
[0122] Synthesis Example 1 (Synthesis of sodium 3-[(2,3-dihydrothieno[3,4-b]-[1,4]dioxin-2-yl)methoxy]-1-methyl-1-propanesulfonate)
[0123] [ka]
[0124] Under a nitrogen atmosphere, 0.437g (10.9mmol) of 60% sodium hydride and 37mL of toluene were charged into a 100mL eggplant flask, and then 1.52g (8.84ml) of (2,3-dihydrothieno[3,4-b][1,4]dioxin-2-yl)methanol was added. The mixture was then heated to reflux temperature while stirring, and stirred at this reflux temperature for 1 hour. Then, while continuing the reflux, a mixture consisting of 1.21g (8.89mmol) of 2,4-butanesultone and 10mL of toluene was added dropwise, and then stirred at the reflux temperature for another 2 hours. After cooling, the resulting reaction liquid was dropped into 160mL of acetone to perform reprecipitation. The resulting powder was filtered and vacuum dried to obtain 1.82g of pale yellow powder in a yield of 62%.
[0125] NMR measurement confirmed that this was sodium 3-[(2,3-dihydrothieno[3,4-b]-[1,4]dioxin-2-yl)methoxy]-1-methyl-1-propanesulfonate represented by the above formula (6).
[0126] 1H-NMR(D2O)δ(ppm);6.67(s,2H),4.54-4.60(m,1H),4.45(dd,1H,J=12.0,2.2Hz),4.26(dd,1H,J=12 .0,6.8Hz),3.90-3.81(m,4H),3.10-3.18(m,1H),2.30-2.47(m,1H),1.77-1.92(m,1H),1.45(d,3H).
[0127] 13 C-NMR(D2O)δ(ppm);14.91,31.22,53.13,66.18,69.18,73.29,73.36,100.81,100.94,140.88,141.06.
[0128] Synthesis Example 2 Synthesis of polythiophene (A) [polymer containing structural units represented by the following formulas (7) and (8)].
[0129] [ka]
[0130] [ka]
[0131] In a 500 ml separable flask, 10 g (30 mmol) of 3-[(2,3-dihydrothieno[3,4-b]-[1,4]dioxin-2-yl)methoxy]-1-methyl-1-propanesulfonic acid sodium salt synthesized according to Synthesis Example 1 and 150 g of water were added. After dissolution, 2.94 g (18.1 mmol) of anhydrous iron(III) chloride was added at room temperature and stirred for 20 minutes. Then, a mixed solution consisting of 14.5 g (60.4 mmol) of sodium persulfate and 100 g of water was added dropwise while maintaining the reaction solution temperature at 30° C. or less. Next, after stirring at room temperature for 3 hours, the reaction solution was dropped into 800 g of acetone to precipitate a black Na-type polymer. The polymer was filtered and dried under vacuum to obtain 18.0 g of crude polymer of sodium 3-[(2,3-dihydrothieno[3,4-b]-[1,4]dioxin-2-yl)methoxy]-1-methyl-1-propanesulfonate.
[0132] Next, 700 g of the aqueous solution of 725 g prepared by adding water to 14.5 g of the crude polymer to a solid content of 2 wt % was passed through a column packed with 200 mL of cation exchange resin Lewatit MonoPlus S100 (H type) (space velocity = 1.1) to obtain 738 g of an aqueous polymer solution of H type. Furthermore, this aqueous polymer solution was purified by cross-flow ultrafiltration (filter = Vivaflow 200, molecular weight cutoff = 5,000, permeability = 5) to obtain 698 g of an aqueous solution of a deep ultramarine color of a polymer containing structural units represented by the above formulas (7) and (8). The amount of polymer (solid content) contained in the aqueous polymer solution was 0.74 wt %. In addition, when ICP-MS analysis was performed, the aqueous polymer solution contained 44 ppm of iron ions and 12 ppm of sodium ions based on the solid content.
[0133] Example 1. 20.67g of conductive polymer aqueous solution containing 1.2% by weight of polythiophene (A) obtained by a method conforming to Synthesis Example 2 was mixed with 3.47g of polystyrene sulfonic acid (B) [manufactured by Aldrich / Mw=75,000, 18% by weight aqueous solution], 0.50g of 3-glycidoxypropyltrimethoxysilane (C), 0.25g of ethylene glycol as a water-soluble compound (E), and 0.12g of water, and the mixture was thoroughly stirred to obtain a conductive polymer aqueous solution with a solid content concentration of 5.5% by weight. The conductivity of the film prepared from this conductive polymer aqueous solution was 20S / cm, and in the water resistance test, the conductive film did not dissolve in water or fall off from the substrate, showing good water resistance. In addition, the SR / SR0 after the heat resistance test was stable at 1.0, showing good heat resistance.
[0134] Example 2. 16.67 g of conductive polymer aqueous solution containing 1.5 wt% polythiophene (A) obtained by a method conforming to Synthesis Example 2 was mixed with 0.69 g of polystyrene sulfonic acid (B) [manufactured by Aldrich / Mw=75,000, 18 wt% aqueous solution], 0.05 g of 3-glycidoxypropyltrimethoxysilane (C), 5.00 g of ethylene glycol as a water-soluble compound (E), and 2.59 g of water, and the mixture was thoroughly stirred to obtain a conductive polymer aqueous solution with a solid content concentration of 1.7 wt%. The conductivity of the film prepared from this conductive polymer aqueous solution was 182 S / cm, and in the water resistance test, the conductive film did not dissolve in water or fall off from the substrate, showing good water resistance. In addition, the SR / SR0 after the heat resistance test was stable at 1.1, showing good heat resistance.
[0135] Example 3. The same procedure as in Example 1 was repeated except that 3-glycidoxypropyltrimethoxysilane (C) was used instead of 3-glycidoxybutyltrimethoxysilane (C). The electrical conductivity of the film made from this conductive polymer aqueous solution was 18 S / cm, and the conductive film did not dissolve in water or fall off from the substrate in the water resistance test, showing good water resistance. In addition, the SR / SR0 after the heat resistance test was stable at 1.0, showing good heat resistance.
[0136] Example 4. The same procedure as in Example 2 was repeated except that 3-glycidoxypropyltrimethoxysilane (C) was used instead of 3-aminopropyltrimethoxysilane (C). The electrical conductivity of the film made from this conductive polymer aqueous solution was 156 S / cm, and the conductive film did not dissolve in water or fall off from the substrate in the water resistance test, showing good water resistance. In addition, the SR / SR0 after the heat resistance test was stable at 1.0, showing good heat resistance.
[0137] Comparative Example 1 An experiment was carried out in accordance with the method of Example 1, except that 3.97 g of water was used instead of 3.47 g of polystyrene sulfonic acid (B) [manufactured by Aldrich / Mw=75,000, 18 wt % aqueous solution] and 0.50 g of 3-glycidoxypropyltrimethoxysilane (C) in Example 1. The conductive film produced from this conductive polymer aqueous solution was not dissolved in the water resistance test, but detachment of the coating film from the substrate was observed, and therefore it was judged to be defective.
[0138] Comparative Example 2 Except for using 0.5 g of water instead of 0.50 g of 3-glycidoxypropyltrimethoxysilane (C), the experiment was conducted in accordance with the method of Example 1. The conductive film prepared from this conductive polymer aqueous solution did not dissolve in the water resistance test, but detachment of the coating film from the substrate was observed, so it was judged to be defective.
[0139] Comparative Example 3. The same procedure as in Example 1 was repeated except that polythiophene (A) was replaced with commercially available PEDOT:PSS (aqueous solution with a concentration of 1.2 wt%, manufactured by Aldrich Co.) The conductive film made from this aqueous conductive polymer solution had good water resistance, but the electrical conductivity was only 0.5 S / cm, and the SR / SR0 after the heat resistance test was 3.4, a larger change than that of the conductive film of the present invention.
[0140] [Table 1]
[0141] Coatings made from these aqueous solutions of conductive polymers exhibit the unexpected advantage of being able to impart water resistance and heat resistance while maintaining electrical conductivity.
[0142] A conductive polymer film produced using the conductive polymer aqueous solution of the present invention exhibits the unexpected and exceptional effects of being superior in heat resistance and water resistance and capable of maintaining high electrical conductivity, as compared with those produced using conventionally known conductive polymer aqueous solutions.
[0143] The conductive polymer film and coated article formed from the conductive polymer aqueous solution of the present invention have high conductivity and are therefore expected to be used as an antistatic film and a solid electrolyte in a solid electrolytic capacitor. [Industrial Applicability]
[0144] The conductive polymer aqueous solution of the present invention is a conductive polymer aqueous solution having excellent adhesion to substrates such as polymers, metals, and glass, and further, since the conductive polymer aqueous solution forms a good conductive polymer film, it can be used as a conductive coating agent (antistatic agent) and a solid electrolyte (cathode material) for solid or hybrid electrolytic capacitors. In particular, since the conductive polymer aqueous solution has excellent adhesion between the dielectric and the conductive layer, water resistance, and heat resistance, which are issues in tantalum and aluminum solid electrolytic capacitors, it can provide a capacitor with high durability and high reliability. In addition, a coated article made of a polymer substrate coated with the conductive polymer film can be used as an antistatic film and a separator for a wound aluminum electrolytic capacitor. In addition, it can be expected to be applied to electrochromic elements, transparent electrodes, transparent conductive films, thermoelectric conversion materials, chemical sensors, actuators, electromagnetic wave shielding materials, and hole transport materials used in organic electroluminescence and solar cell applications.
Claims
1. A conductive polymer aqueous solution containing a polythiophene (A) containing at least one structural unit selected from the group consisting of a structural unit represented by the following general formula (1) and a structural unit represented by the following general formula (2), a polystyrene sulfonic acid compound (B), and a silane compound (C), wherein the content of (A) is 0.01 to 10% by weight, and the contents of (B) and (C) are each independently 0.001 to 30% by weight (however, this conductive polymer aqueous solution excludes a conductive polymer aqueous solution containing a poly(3,4-ethylenedioxythiophene derivative) represented by the following general formula (3a): 【Chemistry 1】 [In the general formulas (1) and (2), R 2 represents a hydrogen atom, a methyl group, an ethyl group, a linear or branched alkyl group having 3 to 6 carbon atoms, or a fluorine atom, m represents an integer of 1 to 10, and n represents 0 or 1. 【Chemistry 2】 [In general formula (3a), R 3 represents a hydrogen atom, an alkyl group having 1 to 6 carbon atoms, a substituted alkyl group having 1 to 6 carbon atoms, an alkoxy group having 1 to 6 carbon atoms, or a substituted alkoxy group having 1 to 6 carbon atoms.]
2. 2. The conductive polymer aqueous solution according to claim 1, wherein the polystyrene sulfonic acid compound (B) has an average molecular weight of 1,000 to 1,000,000.
3. 3. The conductive polymer aqueous solution according to claim 1, wherein the polystyrene sulfonic acid compound (B) is polystyrene sulfonic acid which may have a substituent, a metal salt thereof, or an amine salt thereof, or a copolymer of a styrene sulfonic acid monomer which may have a substituent and another different monomer, a metal salt thereof, or an amine salt thereof.
4. 2. The conductive polymer aqueous solution according to claim 1, wherein the silane compound (C) is an alkoxysilane compound having at least one substituent selected from the group consisting of an epoxy group and an amino group.
5. 5. A method for producing a film, comprising applying the conductive polymer aqueous solution according to claim 1 onto a support and then drying the applied solution.
6. A film comprising a polythiophene (A) containing at least one structural unit selected from the group consisting of a structural unit represented by the following formula (1) and a structural unit represented by the following formula (2), a polystyrene sulfonic acid compound (B), and a silane compound (C) (however, excluding a film containing a poly(3,4-ethylenedioxythiophene derivative) represented by the following general formula (3a): 【Chemistry 3】 [In the general formulas (1) and (2), R 2 represents a hydrogen atom, a methyl group, an ethyl group, a linear or branched alkyl group having 3 to 6 carbon atoms, or a fluorine atom, m represents an integer of 1 to 10, and n represents 0 or 1. 【Chemistry 4】 [In general formula (3a), R 3 represents a hydrogen atom, an alkyl group having 1 to 6 carbon atoms, a substituted alkyl group having 1 to 6 carbon atoms, an alkoxy group having 1 to 6 carbon atoms, or a substituted alkoxy group having 1 to 6 carbon atoms.]
Citation Information
Patent Citations
Conductor, conductive sheet, and touch panel
JP2014013708A
Aqueous conductive polymer solution and conductive polymer film
JP2015063652A
Aqueous conductive polymer solution and conductive polymer film
JP2015157923A
Conductive composition and its application
JP2018090755A
Aqueous conductive polymer solution and conductive polymer film
JP2019196443A